Anti-infective Medicines Use in Children and Neonates With Pre-existing Kidney Dysfunction: A Systematic Review - Minotti, Chiara; Barbieri, Elisa; Doni, Denis; Impieri, Cristina; Giaquinto, Carlo; Donà, Daniele (Frontiers in Pediatrics, 2022)
Background: Dosing recommendations for anti-infective medicines in children with pre-existing kidney dysfunction are derived from adult pharmacokinetics studies and adjusted to kidney function. Due to neonatal/pediatric age and kidney impairment, modifications in renal clearance and drug metabolism make standard anti-infective dosing for children and neonates inappropriate, with a risk of drug toxicity or significant underdosing. The aim of this study was the systematic description of the use of anti-infective medicines in pediatric patients with pre-existing kidney impairment. Methods: A systematic review of the literature was conducted according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The EMBASE, Medline and Cochrane databases were searched on September 21st, 2021. Studies in all languages reporting data on pre-defined outcomes (pharmacokinetics-PK, kidney function, safety and efficacy) regarding the administration of anti-infective drugs in children up to 18 years with pre-existing kidney dysfunction were included. Results: 29 of 1792papers were eligible for inclusion. There were 13 case reports, six retrospective studies, nine prospective studies and one randomized controlled trial (RCT), reporting data on 2168 pediatric patients. The most represented anti-infective class was glycopeptides, with seven studies on vancomycin, followed by carbapenems, with five studies, mostly on meropenem. Antivirals,aminoglycosides and antifungals counted three papers, followed by combined antibiotic therapy, cephalosporins, lipopeptides with two studies, respectively. Penicillins and polymixins counted one study each. Nine studies reported data on patients with a decreased kidney function, while 20 studies included data on kidney replacement therapy (KRT). Twenty-one studies reported data on PK. In 23 studies, clinical outcomes were reported. Clinical cure was achieved in 229/242 patients. There were four cases of underdosing, one case of overdosing and thirteen reported deaths. Conclusion: This is the first systematic review providing evidence of the use of anti-infective medicines in pediatric patients with impaired kidney function or requiring KRT. Dosing size or interval adjustments in pediatric patients with kidney impairment vary according to age, critical illness status, decreased kidney function and dialysis type. Our findings underline the relevance of population PK in clinical practice and the need of developing predictive specific models for critical pediatric patients.